JENIS-JENIS ALGA EPILITIK PADA SUMBER AIR PANAS DAN ALIRANNYA DI KAWASAN CAGAR ALAM RIMBO PANTI KABUPATEN PASAMAN - Widiana, Rina; Abizar, Abizar; Wahyuni, Sri (IAIN Batusangkar, 2011)
Epilitik algae is part of perifitik microalgae which live by sticking on any subtracts such as; rock, coral, and other solid material under water. Algae has green pigment which is called chlorophyll so it can do photosynthetic. Some epilitik algae can adapt in his living place. Cyanophyta is one of algae which lives in any type of habitas such as; pond, stream even land. It can live in middle or extreme temperature. Thus this research was conducted for any kind of epilitik algae in hot water source and its stream in Rimbo Panti reservation in Pasaman. The research was conducted on June 2010 in survey method. The sample was identified in Biology laboratory of Biology department in STKIP PGRI West Sumatera. The concentration measuring of sulfur, nitrogen, and phosphate was done in water laboratory of environment technique department of technical faculty of Andalas university Padang. The parameter which was used are species. Iden-tification key, description, photo specimen, temperature, pH, the concentration of sulfur, nitrogen, phosphate, and dissolved oxygen (DO). It was found that there are 11 kinds of epilitik algae where three are categorized as chrysophyta division and eight as Cyanophyta. In the first station there were 3 epilitik algae and 9 epilitik algae at the second station. The major species which were found in 90o C are Navicula tenella, Ropalodia gibberula and Oscillatoria minima. Thus, it was found that the total number of species in each station is different. Epilitik algae was mostly found in hot water source and only few of them was found in its stream.Key words: epilitik algae, hot water source